2017
DOI: 10.1097/sla.0000000000001945
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of In-hospital Postoperative Opioid Overdose After Major Elective Operations

Abstract: Objective: To describe national trends and outcomes of in-hospital postoperative opioid overdose (OD) and identify predictors of postoperative OD. Summary Background Data: In 2000 the Joint Commission recommended making pain the 5th vital sign, increasing the focus on postoperative pain control. However, the benefits of pain management must be weighed against the potentially lethal risk of opioid OD. Methods: This is a retrospective multi-institutional cohort study of patients undergoing one of six major e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 20 publications
6
54
3
1
Order By: Relevance
“…Our study indicates that advanced age (≥65 years old), being in an ICU, renal impairment and concomitant use of CNS depressants increase the likelihood of having an opioid overdose among hospitalized patients. The results of this study are similar to what was found in previous large study of more than 11 million patients undergoing a major selective operation: advanced age (≥60 years old) and renal disease were predictors, with renal disease being the strongest comorbid predictor (OR 2.89, 95% CI 2.45‐3.41) after history of substance use disorders (OR 14.81, 95% CI 12.74‐17.21) . We excluded patients with a documented history of substance use disorder from our study as a potential confounding factor to examine dose‐related effect as this patient population may not reflect the general population and likely have significant tolerance.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study indicates that advanced age (≥65 years old), being in an ICU, renal impairment and concomitant use of CNS depressants increase the likelihood of having an opioid overdose among hospitalized patients. The results of this study are similar to what was found in previous large study of more than 11 million patients undergoing a major selective operation: advanced age (≥60 years old) and renal disease were predictors, with renal disease being the strongest comorbid predictor (OR 2.89, 95% CI 2.45‐3.41) after history of substance use disorders (OR 14.81, 95% CI 12.74‐17.21) . We excluded patients with a documented history of substance use disorder from our study as a potential confounding factor to examine dose‐related effect as this patient population may not reflect the general population and likely have significant tolerance.…”
Section: Discussionsupporting
confidence: 86%
“…According to a recent study of more than 11 million patients undergoing a major inpatient operation between 2002 and 2011, the in‐hospital mortality rate was more than 4 times higher in the group of patients who had a postoperative opioid overdose compared to those who did not (1.7% vs 0.4%, P < .001). Hospital length of stay and total healthcare cost were also significantly greater for patients who had a postoperative overdose than those who did not (6.7 vs 3.9 days; $83 655 vs $46 255; P < .001) …”
Section: What Is Known and Objectivementioning
confidence: 98%
See 2 more Smart Citations
“…Obtaining sufficient postoperative pain control can also allow for earlier mobilization and has the ability to shorten a patient's LOS thereby decreasing hospital costs [3,4]. The current standard therapy for postoperative pain management consists of opioid medications, however, with the current epidemic of overdoses and abuse, physicians must consider the potential risks when formulating a postoperative pain regimen [5,6]. The importance of postoperative pain control and potential detrimental side-effects of opioid medications lends to the importance of finding alternative analgesic interventions with improved adverse-effect profiles [7].…”
Section: Introductionmentioning
confidence: 99%